Prevalence of thyroid dysfunction and its relationship with the lipid profile in patients in hospital from Encarnación - Génez Yeza, Edith Noemí (2021)
Fil: Génez Yeza, Edith Noemí. Hospital Regional de Encarnación; Paraguay.